Reactive Power Control in AC Power Systems Fundamentals and Current Issues - Mahdavi Tabatabaei, Naser; Jafari Aghbolaghi, Ali; Bizon, Nicu; Blaabjerg, Frede (Power Systems, 2017)
XXXVI, 634 p. 350 illus., 101 illus. in color.